DUALITAS STRUKTUR PERTANIAN DAN PEMBANGUNAN PARIWISATA (STUDI KASUS DI DESA ORO-ORO OMBO KECAMATAN BATU KOTA BATU) - Winarsih, Siti Nurul Fitriyah; Susilo, Rachmad K. Dwi; Hayat, Muhammad (UNIVERSITAS SEBELAS MARET (UNS), 2023)
Batu City was originally famous for its branding as the City of Apples which lifted from the structure, but with the change of the Mayor of Batu, Batu City has changed the direction of the development of Batu City into an agricultural-based tourism city. The actors have used the traditional structure of agriculture into a new structure for tourism development. This study aims to explain the duality of agricultural structures and tourism development in Oro-oro Ombo Village, Batu District, Batu City. The researcher uses a qualitative research approach with the type of case study research. Determination of the selected subjects using snowball sampling technique. Collecting data using observation, interview, and documentation techniques. The data analysis technique uses time series analysis. Anthony Giddens’ structuration theory is used as a supporting equipment for research analysis. The results of the research are as follows: (1) The presence of a new structure in the form of development and encouraging farmers in Oro-oro Ombo Village to sell agricultural land to investors. (2) Actors who used to play an active role in the agricultural structure are now shifting to become actors in the tourism structure. (3) The duality of the agency-structure relationship which is characterized by the bargaining conditions that occur, the structure of agriculture and tourism in Oro-oro Ombo Village attracts each other (constrains), actually can help each other but the actors involved in the two structures still do not know how.Keywords: Actor, Agriculture, Duality of Structure, and Tourism AbstrakKota Batu semula terkenal dengan branding Kota Apel yang mengangkat eksistensi dari struktur pertanian, namun dengan bergantinya periode pemerintahan Wali Kota Batu telah mengubah arah pembangunan Kota Batu menjadi kota pariwisata berbasis pertanian. Para aktor telah menggeser struktur tradisional berupa pertanian menjadi struktur baru pembangunan pariwisata. Penelitian ini bertujuan menjelaskan bentuk dualitas struktur pertanian dan pembangunan pariwisata di Desa Oro-oro Ombo, Kecamatan Batu, Kota Batu. Peneliti menggunakan pendekatan penelitian kualitatif dengan jenis penelitian studi kasus. Penentuan subjek dipilih menggunakan teknik snowball sampling. Pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan analisis deret waktu. Teori Strukturasi Anthony Giddens digunakan sebagai alat pendukung analisis penelitian. Hasil penelitian adalah sebagai berikut: (1) Hadirnya struktur baru berupa pembangunan pariwisata mendorong petani di Desa Oro-oro Ombo untuk menjual lahan pertanian kepada para investor. (2) Aktor yang dulu aktif berperan dalam struktur pertanian kini bergeser peran menjadi aktor dalam struktur pariwisata. (3) Dualitas hubungan struktur-agensi ditandai dengan kondisi tawar menawar yang terjadi, struktur pertanian dan struktur pariwisata di Desa Oro-oro Ombo saling tarik menarik (constrain), sebenarnya bisa saling menunjang namun aktor yang terlibat di kedua struktur tersebut masih belum tahu harus bagaimana.Kata Kunci : Aktor, Dualitas Struktur, Pariwisata, dan Pertanian